Narration as a means of communication In selected novels by j. M. Coetzee: waiting for The barbarians and foe - Wan Mazlini Othoman (Tanjong Malim, 2019)
Narration as a means of communication In selected novels by j. M. Coetzee: waiting for The barbarians and foe by Wan Mazlini Othoman